Challenging the emerging narrative: Critical examination of coalmining safety in China, and recommendations for tackling mining hazards. (June 2015) - Geng, Fan; Saleh, Joseph Homer
Highlights: We provide a synthesis of key characteristics of coalmining in China. We challenge the newly emerged safety narrative in China. We found evidence of significant underreporting of fatalities in coalmining accidents. Official fatality statistics may underestimate the actual numbers by a factor of 5. We provide recommendations for prioritizing and tackling coalmining hazards. Abstract: Coal mining remains a dangerous occupation worldwide, and in China where this industry is strategically important for the country's economic development, its safety track record is particularly gruesome. Between 1990 and 1999, thousands of small and large-scale accidents in Chinese underground coalmines have caused over a reported sixty thousand fatalities. To tackle this significant problem, several laws were passed in support of mining safety, and two major institutional innovations were adopted in the late 1990s and early 2000s: the establishment of the State Administration of Coal Mine Safety (SACMS) and the State Administration of Work Safety (SAWS), the former is subsumed under the latter. Since the establishment of SAWS/SACMS, a new safety narrative has emerged, which posits that significant safety improvements have occurred over the last decade in Chinese coalmines, and that these improvements are the result of effective government policy and safety regulations. The findings in this work, based on publically available official data, challenge this new safety narrative on several fronts. For example, we found evidence of significant under-reporting of fatality numbers in coal mining accidents. We also found that mining accidents are sometimes (mis)classified as "natural disasters", and as a result, their fatality numbers are not tallied in the official statistics. We assessed that the official fatality statistics may underestimate the actual fatality numbers by a factor ranging from 3 to 5. More importantly, we found it doubtful that safety improvements have occurred in operating Chinese coalmines since 2000. We inferred that the reduction in total fatality and accident numbers could be explained by the closure of small mines or the exclusion of their fatality statistics. We concluded with some recommendations and a list of coal mining hazards prioritized for targeted safety interventions and improvements.